2008
DOI: 10.1210/jc.2008-0823
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Structure Are Affected in Childhood Obesity

Abstract: Obese children frequently show alterations of thyroid structure and function that are not completely explained by the presence of an autoimmune involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
3
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 32 publications
10
84
3
8
Order By: Relevance
“…After weight loss, a reduction in thyroid volume was also observed (60). Studies on children and adults also demonstrated that obesity is associated with a thyroid hypo-echogenic pattern at US, which occurs independently from thyroid autoimmunity (77,78). Indeed, among all patients with a thyroid hypo-echogenic pattern of the gland, only a minority of those with morbid obesity (20%) had serological evidence of thyroid autoimmunity (78).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 98%
See 1 more Smart Citation
“…After weight loss, a reduction in thyroid volume was also observed (60). Studies on children and adults also demonstrated that obesity is associated with a thyroid hypo-echogenic pattern at US, which occurs independently from thyroid autoimmunity (77,78). Indeed, among all patients with a thyroid hypo-echogenic pattern of the gland, only a minority of those with morbid obesity (20%) had serological evidence of thyroid autoimmunity (78).…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 98%
“…Other studies reported an increased prevalence of humoral signs of thyroid autoimmunity in childhood obesity. Radetti et al (77) found high levels of TPOAb in nearly 24% of overweight or obese children. This prevalence is similar to that observed in children with type 1 diabetes mellitus (21.6%) (123) and outnumbers current epidemiologic data in iodine-sufficient schoolchildren, which indicate a TPOAb prevalence in the range of 3.4-4.6% (124,125).…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…Little has been reported on the morphology of the thyroid gland in adults with morbid obesity (20,21). A recent study, performed in obese children, showed for the first time that obesity is associated with structural changes in thyroid morphology, as assessed by US, which are unrelated to thyroid autoimmunity (22). The aim of the current study was to evaluate the diagnostic accuracy of thyroid US for the detection of thyroid autoimmune diseases in adult patients with morbid obesity.…”
Section: Introductionmentioning
confidence: 93%
“…se ha demostrado la asociación entre niveles de tsh y exceso de peso corporal 7,8,16,19,21,29,[35][36][37] , con los cuales concuerda la correlación directa e independiente entre tsh y zimc encontrada en el presente estudio. esta relación no se encontró en otra publicación nacional, probablemente debido a que ésta incluyó solamente pacientes eutiroideos con una muestra de menor tamaño 38 .…”
Section: Discussionunclassified
“…sin embargo, en otros estudios se ha descrito la presencia de anticuerpos anti-tiroideos en 12-20% de los obesos 36,43 . esto último, junto a la alta prevalencia de tiroiditis crónica linfocitaria o de hashimoto en mujeres adultas en Chile, podría explicar que ambos factores pueden coexistir, siendo ello más probable en las mujeres, como ocurrió en nuestro estudio, en que se encontró asociación directa entre estado nutricional en niñas y tsh plasmática 44,45 .…”
Section: Discussionunclassified